UTILIZATION OFWASTE IN LIEU MSG SHRIMP HEAD IN THE MAKING SEASONING FRIED RICE INSTANT - Susilowati Susilowati (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
In the emerging market sold fast instant bumu either wet or dry . Another advantage ofinstant seasoning is more efficient especially in the form of flour . By using instant seasonin wecan cook anything no longer need to buy other spices. (MSG) as a flavoring agent, the PublicInterest Research and Advocacy Center (PIRAC) which questioned the content of monosodiumglutamate, aka MSG in regular snacks consumed by children. According to non-governmentalorganizations , many packaged snacks are not included in the MSG content that could threatenthe health of children.Fried rice is a popular and well-liked food both young and old , rich and poor . friedrice requirement of MSG. For the shrimp head wastes would I use as an alternative to MSG thatfried rice is safe to eat the children . This study aims to determine the difference in taste andcolor of fried rice with shrimp heads use the amount of waste that is different .This type of research is the study of laboratory experiments with the manufacture ofinstant fried rice seasoning , in this study using shrimp head weight 5 g, 10 g , 15 g , 20 g , 25 gand fried rice control by using MSG . Data Collection Techniques with experimental methods ,organoleptic test. With Scale Parameters flavor, color. Technique 1 Factor ANOVA dataanalysis , SPSS 17, the obtained results are differences in taste and color of fried rice withshrimp heads using different wasteIt can be concluded 1. There is a difference in the taste of fried rice with shrimp headsuse the number of different waste as a substitute for MSG in the making fried rice seasoning 2.There are differences in the color of fried rice with shrimp heads use the number of differentwaste as a substitute for MSG in the making fried rice seasoning.